Mobilization of Cyber Extension Participants to Build Household Food Security - Metha Madonna; Sumardjo Sumardjo; Siti Amanah; E Oos M Anwas (Jurnal Penelitian Pendidikan IPA, 2022)
Youtuber, Tiktokers and content creater exist on internet who actively showing agricultural information in limited land, hydroponic cultivation also tips for utilization home yard as plantation productive a form public participation in an attempt to increase agricultural in micro scale. The impressions agricultural innovative and creatives from content creators in internet is a phenomenon change occurs paradigm education present that openly also no need to rely on employment of counseling functional with status State Civil Apparatus. Absence content creator information about alternative agricultural can categorize to participant cyber extension in order to build food resilience at the household level. Cyber extension that is conducted on public became concept participative counceling that are relevant developed when limited quantity human resources agricultural counselors, procurement material and support facilities. Purpose: studies on existence participant cyber extension to design programs and strategy mobilize content creator into intensify extension utilization home yard to plant productive to build food resilience household. This study improving concept couceling based society and mobilization power source theory. Method: systematics literatur review with qualitative approach. Result: (1) Need to be given coaching or mentoring for participants especially content creator to produce mater that are educative and solutive for society who want start plating at home yard (2) Giving appreciation or reward to participant who active and creatuve doing cyber extension